A link between β-catenin and hypertrophy: evaluation and meta-analysis - Palchevska, O.L.; Macewicz, L.L.; Piven, O.O. (Вiopolymers and Cell, 2016)
Heart is a terminally differentiated organ almost unable to regenerate. The remodeling and hypertrophic growth are believed to be the main mechanisms of heart renovation after workloads or injury. Although there have been major advances in the identification of the genes and signaling pathways involved in mediating hypertrophy, further characterization of the underlying molecular mechanisms is needed due to the overall complexity of this process. Aim. The present work is an attempt to systematically assess the previous research on a β-catenin role in the heart muscle hypertrophy development. We hypothesized that β-catenin is a member of universal and conserved regulatory pathway for different tissues and species. To test this hypothesis, we performed the meta-analysis of experimental data available in different databases. Methods. The literature data were analyzed via Origin 8.0 using the simple regression and two-way ANOVA methods. Results. The results allowed selecting the most reproducible hypertrophy markers which were appropriate for the study of β-catenin function in the hypertrophy response (SERCA, actin DIF, Axin-2, c-myc, CD1, BNP, ANP and total protein/DNA index). The analysis shows that a decrease in the β-catenin expression has an ambiguous effect on heart hypertrophy. Conclusion. We have drawn interesting conclusions on the model and species-specific link between the β-catenin level and hypertrophy development, as well as between some hypertrophic markers and β-catenin expression on one hand, and hypertrophy development etc. on the other hand. The results also allowed selecting the most reproducible hypertrophy markers.